Investigating the delivery of health improvement interventions through professional football club community trusts-strengths and challenges - A.R. Pringle; S. Zwolinsky; L. Lozano-Sufrategui (Elsevier, 2021)
Objectives: This study audits health improvement provision delivered in/by English professional Football Club Community Trusts and reports the strengths and challenges around the implementation of interventions. Study design: Multi-methods design: Data were collected through (i) a review of trust websites (n ​= ​72), (ii) an online survey (n ​= ​34/47.2%) and (iii) semi-structured interviews (n ​= ​11/32.3%) with a sub-sample of trust managers. Results: The review of websites confirms all trusts provided physical activity-led interventions. The online survey showed most managers were male (n ​= ​23/67.7%) and white British (n ​= ​30/88.2%). Two thirds held management roles, (n ​= ​23/67.6%) and represented Championship (n ​= ​12/35.2%), League 1 (n ​= ​13/38.2%) and League 2 clubs (n ​= ​9/26.5%). Trusts provided physical activity and most provided diet (n ​= ​31/91.2%) as well as smoking (n ​= ​20/58.8%) and alcohol (n ​= ​19/55.9%) interventions. Weight management, (n ​= ​25/73.5%), mental health interventions (n ​= ​28/82.4%) were offered. Trusts provided male-specific (n ​= ​20/58.8%), with fewer providing female-specific interventions (n ​= ​15/44.1%). Most trusts (n ​= ​30/88.2%) evaluated interventions. 80.8% (n ​= ​21/26) used public health guidance for programme design, 69.2% (n ​= ​18/26) delivery, 57.7% (n ​= ​15/26) needs assessment and 50% (n ​= ​13/26) evaluation. Interviews and qualitative reports identified strengths including, using football, the 'club brand', 'meeting health needs' and 'working as a strategic collaboration with partners'. Challenges included 'short-term funding staffing, mainstreaming, and evaluating interventions'. Conclusion: Football Community Trusts deliver interventions, but challenges were encountered when implementing these programmes.